2023
DOI: 10.1071/sh22139
|View full text |Cite
|
Sign up to set email alerts
|

Would men who have sex with men support less frequent screening for asymptomatic chlamydia and gonorrhoea to improve antibiotic stewardship? A qualitative study

Abstract: Background. Men who have sex with men (MSM) taking pre-exposure prophylaxis (PrEP) are recommended to have screening for asymptomatic chlamydia and gonorrhoea every 3 months with high rates of asymptomatic chlamydia and gonorrhoea detected. However, there is little evidence about the effectiveness of this screening interval and there is increasing concern about antibiotic consumption and its impact on antimicrobial resistance. There have been calls to reconsider this frequent screening for chlamydia and gonorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…MSM are often exposed to an excess of antimicrobials, including macrolide, fluoroquinolones, cephalosporins and tetracyclines (Kenyon and Schwartz, 2018). An explanation of the large drug consumption among MSM is the practice of screening for gonorrhea and chlamydia, with high rates of asymptomatic infections detected and treated (Kenyon et al, 2020;Wardley et al, 2023). In this context, it has been observed that the pharyngeal environment of MSM using pre-exposure prophylaxis (PrEP) for HIV prevention is enriched with antibiotic resistance genes (Van Dijck et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…MSM are often exposed to an excess of antimicrobials, including macrolide, fluoroquinolones, cephalosporins and tetracyclines (Kenyon and Schwartz, 2018). An explanation of the large drug consumption among MSM is the practice of screening for gonorrhea and chlamydia, with high rates of asymptomatic infections detected and treated (Kenyon et al, 2020;Wardley et al, 2023). In this context, it has been observed that the pharyngeal environment of MSM using pre-exposure prophylaxis (PrEP) for HIV prevention is enriched with antibiotic resistance genes (Van Dijck et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic use of doxycycline after potential exposures (i.e., DoxyPEP), has been found to be effective in reducing the likelihood of acquiring an STI in men who have sex with men (MSM) ( Luetkemeyer et al, 2023 ). However, frequent use of antibiotics has been correlated with antimicrobial resistance causing public health concerns, particularly for groups who screen frequently ( Kenyon, 2018 , Wardley et al, 2023 ). Vaccinations to reduce the incidence of bacterial STIs are still under investigation but may offer an alternative ( Gottlieb et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%